Regulatory Monitoring Systems of Fortified Salt and Wheat Flour in Selected Asean Countries. Issue 2 (June 2013) - van den Wijngaart, Annoek; Bégin, France; Codling, Karen; Randall, Philip; Johnson, Quentin W.
Background: Considerable efforts have been made over the past decade to address vitamin and mineral deficiencies. An increasing number of countries in the Association of Southeast Asian Nations (ASEAN) are adopting mandatory food fortification as one of the primary strategies to overcome these deficiencies. Experience shows that fortified foods can reach large parts of the population, including the poor, if the fortification is done on a mandatory rather than a voluntary basis and if the food vehicle is widely consumed. Objective: To review the importance of regulatory monitoring as an essential component of food fortification efforts in selected ASEAN countries, with special focus on the available information on regulatory monitoring systems for iodized salt and fortified wheat flour. Methods: The role of regulatory monitoring in strengthening food fortification programs was discussed during a joint regional meeting of the World Health Organization, UNICEF, the Flour Fortification Initiative, the Global Alliance for Improved Nutrition, the Micronutrient Initiative, and the World Bank on regulatory monitoring of salt and wheat flour fortification programs in Asia, which took place in Manila, Philippines, on 27–29 September 2011. This paper reviews the regulatory monitoring systems of selected ASEAN countries that participated in this meeting. Results: Problems and challenges in regulatory monitoring systems for iodized salt and fortified wheat flour in selected ASEAN countries are identified, and a description of the role of regulatory monitoring in strengthening food fortification initiatives, particularly of salt and flour, and highlights of areas for improvement are presented. Conclusions: Regulatory monitoring consists of monitoring activities conducted at the production level, at customs warehouses, and at retail stores by concerned regulatory authorities, and at the production level by producers themselves, as part of quality control and assurance efforts. Unless there are appropriate enforcement and quality assurance mechanisms in place to stimulate compliance by food producers, i.e., regulatory monitoring, having national legislation will not necessarily lead to increased coverage of fortified products and associated outcomes.